(untitled) (Revista do LabDGE - UFF, 2023)
This research aims the identification of the theoretical benefits of Toyota Kata implementation. This analyze was done through a theoretical, combined, descriptive and bibliographic research, carried out through a literature review. To clarify these benefits, improvement kata and coaching kata was described according to the literature review. As this is a literature review of a subject of general implementation, the macro results of this research suggest as benefits, the creation of knowledge and organizational culture having as secondary results the efficiency improving and waste reduction. The results obtained will culminate in operational results such as the increase in the quality of services, growth in production volume, besides the tasks optimization and success in solving problems, which are typical characteristics of Toyota Kata, for involving people and routines, promoting a better engagement. This research showed also, when applied in its essence, Toyota Kata is an effective continuous improvement mechanism within organizations.